Subsidiarity and Economic Reform in Europe - Gelauff, George; Grilo, Isabel; Lejour, Arjan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
Subsidiarity in the European Union, as the guiding principle of decision-making "close to the people", is often motivated and discussed from a predominantly political perspective. In this book, twenty-five renowned economic researchers and policy experts draw the demarcation between national and European policies from an economic viewpoint. Insights from economic theory and empirical research are used both to analyse the assignment of policies between the EU and its Member States and to identify appropriate levels of decision-making. Four key areas of the renewed Lisbon strategy are highlighted for their policy relevance: education and innovation, the internal market, corporate taxation, and regional and transport policy.
Subsidiarity for Better Economic Reform? -- Assessing Subsidiarity -- Who Shall Decide What? Citizens$1 (BAttitudes Towards Political Decision Making in the EU -- Subsidiarity and Economic Policy -- Higher Education Reform and the Renewed Lisbon Strategy: Role of Member States and the European Commission -- Higher Education, Mobility and the Subsidiarity Principle -- European Coordination of Higher Education -- On the Roles and Rationales of European STI-Policies -- Why European Innovation Policy? -- Integrating Regulated Networks Markets in Europe -- Subsidiarity and the Internal Services Market -- Agriculture Policy: What Roles for the EU and the Member States? -- Tax Policy and Subsidiarity in the European Union -- Coordinating Corporation Taxes in the European Union: Subsidiarity in Action! -- Code of Coordination for Corporate Taxation -- Corporate Income Taxation and the Subsidiarity Principle -- Subsidiarity in Regional Policy -- Regional Policy as a Means to Curb Immigration -- Subsidiarity and Transport Policy in Europe: What EU-Subsidies Do We Need for the TEN?.s
Keywords: European Economic Community literature; Economic policy; Economics; Economic Policy; European Integration; Electronic books